Social adjustment and self- esteem among a sample of visitors and non- visitors to the psychological clinic after being exposed to psychological trauma (Sexual harassment as an example) - Almosawi, Zahraa Hussain; Alkout, Ahmad Fadhel; Akbar, Mohammad Abd Alali (Arab Journal for Sciences and Research Publishing, 2021)
The study aims to investigate the differences between visitors and non- visitors to the psychological clinic after being exposed to psychological trauma (sexual harassment as an example) in Social adjustment and self- esteem, as well as to discover the relationship between study variables among a purposive sample consisted of 54 participants (17=visitors, 37=non- visitors), 31.4% were males. To achieve the study aims two scales were used: Social Adjustment scale by "Sura, E. M." (1986), and Self- esteem scale by "Rosenberg, M." (1965). Results revealed that there were significant differences between visitors and non- visitors to psychological clinic after being traumatized in social adjustment and self- esteem. In addition, the results showed significant correlation between social adjustment and self- esteem among the total sample, visitors and non- visitors of the psychological clinic. The full text of the study includes details of the results and discussion, as well as some of recommendations made by the researchers.